Depression among Community Middle Adulthood Age Groups (Jurnal Keperawatan Jiwa (JKJ): Persatuan Perawat Nasional Indonesia, 2021)
The second peak in the incidence of depression occurs in the middle adulthood age groups. Depression has a more chronic course and poorer prognosis in older adults than in younger and the effect caused impaired well-being. Research on depression in the middle adult group has not been widely carried out and is mostly done in  early adulthood and elderly groups Purpose of the research to identify the level of depression in the middle adulthood age groups.Research method using quantitative research with a descriptive design. The research instrument used depression inventory from Beck Depression Inventory (BDI-II). The sample was selected using a total sampling technique, amounting to 170 respondents. The results showed respondents were studied, 48.8% are men and 51.2% are women. There are 20% of respondents at the level of mild depression, 56.5% of respondents at the level of moderate depression and 4.7% of respondents at the level of major depression. The research results can become basic data that can be developed for mental health services in the community at the primary health level.